Shell Shocked: a peak into the thermal tolerance and shell utilization of Clibanarius erythropus - Dominguez, Brookelyn Caitlin (2023)
Thermal tolerance of species has become a topic of increasing interest due to climate change and global warming. This type of data is important for identifying vulnerable species and establishing management strategies. In this study, the thermal tolerance and shell utilization were investigated for the Mediterranean intertidal hermit crab, Clibanarius erythropus in the fast warming southeastern Mediterranean Sea. The thermal tolerance was determined using two methods 1) the critical thermal maximum (CTMax) and 2) physiological performance, with the change in respiration rates used as a performance parameter. Additionally, CTMax was tested for three other intertidal species: the crab Eriphia verrucosa, topshell snail Phorcus turbinatus, and snail Pisania striata in order to make a comparison between the hermit crab and other members of its habitat. It was hypothesized that C. erythropus will have a higher thermal tolerance than the other species in their habitat, and that the size of the hermit crab will correlate with the size of the occupied shell. As expected, the CTMax of C. erythropus (38.8 °C) was found to be higher than the other species. This was followed by E. verrucosa at 37.93 °C, P. striata at 37.48 °C, and P. turbinatus which had a considerably lower value at 34.19 °C. Additionally, C. erythropus was the only species that was found to have a positive thermal safety margin (TSM). The weight of the occupied shell was found to have a significant correlation with the size of the hermit crab. These findings indicate that this species of hermit crab may be better equipped to handle continuous regional warming and intensification of extreme events than the other tested native species. Future work should focus also on other proxies for thermal performance such as degree of mobility and juvenile thermal tolerance.